The Clinical Frailty Scale predicts inpatient mortality in older hospitalised patients with idiopathic Parkinson s disease - Romero-Ortuno, Roman (My University, 2018)
Parkinson’s disease and frailty are both common conditions affecting older people. Little is known regarding the association of the Clinical Frailty Scale with hospital outcomes in idiopathic Parkinson’s disease patients admitted to the acute hospital. We aimed to test whether frailty status was an independent predictor of short-term mortality and other hospital outcomes in older inpatients with idiopathic Parkinson’s disease
PUBLISHED
Keywords: frailty; Parkinson’s disease; Clinical Frailty Scale; frailty; Parkinson’s disease; Clinical Frailty Scale; Ageing